PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP TRANSPARANSI PEMERINTAH DAERAH (Studi pada LKPD di Indonesia Tahun Anggaran 2018 dan 2019) - Yudistira Yudistira; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of local government characteristics on regional government transparency. The independent variables used in this research are the size of the government (SIZE), the quality of financial reports (OPINI), the level of government response (ACCRUAL), and the political environment (POLITICS). This study uses secondary data in the form of financial reports obtained from every official website of the provincial government in Indonesia. This research used purposive sampling method. . The sample of this study consisted of 34 local governments in Indonesia for the 2018-2019 period. The analysis model uses logistic regression analysis. The results of this study indicate that the size of the local government (SIZE) and the political environment (POLITICS) have a positive effect on the transparency of local government. However, the Quality of Financial Statements (OPINI) and Response Level (ACCRUAL) negatively affect local government financial transparency.